Rolling Circle Amplification Tailored for Plasmonic Biosensors: From Ensemble to Single-Molecule Detection - Schmidt, Katharina; Hageneder, Simone; Lechner, Bernadette; Zbiral, Barbara; Fossati, Stefan; Ahmadi, Yasaman; Minunni, Maria; Toca-Herrera, Jose Luis; Reimhult, Erik; Barisic, Ivan; Dostalek, Jakub (ACS applied materials & interfaces, 2022)
We report on the tailoring of rolling circle amplification (RCA) for affinity biosensors relying on the optical probing of their surface with confined surface plasmon field. Affinity capture of the target analyte at the metallic sensor surface (e.g., by using immunoassays) is followed by the RCA step for subsequent readout based on increased refractive index (surface plasmon resonance, SPR) or RCA-incorporated high number of fluorophores (in surface plasmon-enhanced fluorescence, PEF). By combining SPR and PEF methods, this work investigates the impact of the conformation of long RCA-generated single-stranded DNA (ssDNA) chains to the plasmonic sensor response enhancement. In order to confine the RCA reaction within the evanescent surface plasmon field and hence maximize the sensor response, an interface carrying analyte-capturing molecules and additional guiding ssDNA strands (complementary to the repeating segments of RCA-generated chains) is developed. When using the circular padlock probe as a model target analyte, the PEF readout shows that the reported RCA implementation improves the limit of detection (LOD) from 13 pM to high femtomolar concentration when compared to direct labeling. The respective enhancement factor is of about 2 orders of magnitude, which agrees with the maximum number of fluorophore emitters attached to the RCA chain that is folded in the evanescent surface plasmon field by the developed biointerface. Moreover, the RCA allows facile visualizing of individual binding events by fluorescence microscopy, which enables direct counting of captured molecules. This approach offers a versatile route toward a fast digital readout format of single-molecule detection with further reduced LOD.
Keywords: jednovláknová DNA; biosensor; Limit of Detection; povrchová plasmonová rezonance; limita detekce; biosenzitivní techniky; Biosensing Techniques; DNA, Single-Stranded; surface plasmon-enhanced fluorescence; Nucleic Acid Amplification Techniques; techniky amplifikace nukleových kyselin; rolling circle amplification; immunoassays; surface plasmon resonance; single molecule; Surface Plasmon Resonance